2022
DOI: 10.1093/jambio/lxac029
|View full text |Cite
|
Sign up to set email alerts
|

Potentially probioticLimosilactobacillus reuterifrom human milk strengthens the gut barrier in T84 cells and a murine enteroid model

Abstract: Aims At conception, the infant gut barrier is immature, gradually developing with regular intake of maternal milk. This study addressed whether the barrier-strengthening effect of breast feeding might be attributable, at least in part, to autochthonous beneficial human milk bacteria. Methods and results Twelve bacterial strains from the breast milk of Pakistani mothers who underwent cesarean delivery (NPL-88, NPL-157, NPL-179… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…These strains were then tested to determine whether or not they had the ability to act as probiotics. Earlier reports reported that a pH range between 6.2 and 8.5 is most suitable for the development and screening of LAB (Anjum et al, 2023). As shown in the Table 2, a total of 60 LAB strains were isolated from the oral (10 strains) and food samples (50 strains), and then analyzed for their microscopic, macroscopic, biochemical, and contemporary in vitro probiotic characteristics before being subjected to molecular characterization.…”
Section: Discussionmentioning
confidence: 99%
“…These strains were then tested to determine whether or not they had the ability to act as probiotics. Earlier reports reported that a pH range between 6.2 and 8.5 is most suitable for the development and screening of LAB (Anjum et al, 2023). As shown in the Table 2, a total of 60 LAB strains were isolated from the oral (10 strains) and food samples (50 strains), and then analyzed for their microscopic, macroscopic, biochemical, and contemporary in vitro probiotic characteristics before being subjected to molecular characterization.…”
Section: Discussionmentioning
confidence: 99%